Pandemic-Era Grade 3 Numeracy: Strategies for Arithmetic Operations: Numerasi dan Strategi Pelajar Kelas 3 Era Pandemi: Implikasi Operasi Aritmetika Penjumlahan dan Pengurangan - Salshabila , Irdiana Septi; Wardana, Mahardika Darmawan Kusuma (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative study investigates the numeracy ability of 41 grade 3 elementary school students from Geluran II State Elementary School in completing addition and subtraction arithmetic operations during the pandemic era. Data was collected through tests and interviews, and analyzed using Miles and Huberman's model for data reduction, presentation, and conclusion drawing. Results revealed that students employed diverse strategies in performing arithmetic operations, but not all strategies led to correct solutions. While students explained the steps well, errors occurred when the initial mathematical statement was presented inaccurately. This study emphasizes the significance of understanding students' individual approaches and errors in arithmetic problem-solving, shedding light on crucial implications for teaching and learning mathematics in challenging circumstances. Highlights: Differentiated Approaches: Grade 3 students exhibited diverse strategies in solving arithmetic operations. Error Identification: Students' ability to explain steps correctly but make errors in the initial mathematical statement. Pandemic Impact: Understanding numeracy abilities during the pandemic highlights implications for mathematics education. Keywords: Numeracy, Grade 3 Students, Pandemic Era, Arithmetic Operations, Strategies